2003
DOI: 10.1016/s0925-4439(03)00077-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of recombinant rat eosinophil-associated ribonuclease-1 and -2 and analysis of their biological activities

Abstract: Rat eosinophils contain eosinophil-associated ribonucleases (Ears) in their granules. Ears are thought to be synthesized as pre-forms and stored in the granules as mature forms. However, the N-terminal amino acid of mature Ear-1 and Ear-2 is still controversial. Therefore, we prepared two recombinant mature forms of Ear-1 and Ear-2 in which the N-terminal amino acids are Ser24 (S) [Ear-1 (S) and Ear-2 (S)] and Gln26 (Q) [Ear-1 (Q) and Ear-2 (Q)], and analyzed their biological activities by comparing them with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The bactericidal activity of Ss‐RNases was found to be retained when their ribonucleolytic activity was destroyed, as previously described for other bactericidal RNases, such as human RNase 3 and RNase 7, and chicken RNase A‐2 [11,13,29]. A similar result has been reported for rat eosinophils Ear‐1 and Ear‐2 [30], but in those experiments only about 50% of the ribonucleolytic activity was destroyed, and many details of the experiments were not provided.…”
Section: Discussionsupporting
confidence: 80%
“…The bactericidal activity of Ss‐RNases was found to be retained when their ribonucleolytic activity was destroyed, as previously described for other bactericidal RNases, such as human RNase 3 and RNase 7, and chicken RNase A‐2 [11,13,29]. A similar result has been reported for rat eosinophils Ear‐1 and Ear‐2 [30], but in those experiments only about 50% of the ribonucleolytic activity was destroyed, and many details of the experiments were not provided.…”
Section: Discussionsupporting
confidence: 80%
“…The pI of RNASE9 is lower than that of any other mammalian RNASEs. A basic pI RAT RNase9 IN EPIDIDYMIS is believed to be important for RNase activity, conferring the affinity of the enzyme to its negatively charged RNA substrate [26][27][28][29]. Therefore, RNase9 may not function as a typical RNase.…”
Section: Discussionmentioning
confidence: 99%
“…Rat EAR-1 and EAR-2 have been shown to inhibit the growth of E. coli and S. aureus at concentrations as low as 0.3 mM. 81 Antiviral activity has also been reported for the EARs. Moreau and colleagues demonstrated that recombinant EAR-2 reduces the infectivity of pneumonia virus of mice (PVM) in cultured respiratory epithelial cells.…”
Section: Eosinophil-associated Ribonucleasesmentioning
confidence: 99%